(untitled) (International Journal of Pathology, 2020)
The research must be carefully planned. It must answer some specific scientific question and should add something new to the already existent body of scientific knowledge and better understanding of the subject matter. It should not be mere replica of some old research. The aim should be well thought of. The research ought to bring some benefits in terms of improvement in medical care and management! The research must be repeatable and replicable with methods described in sufficient details! Mere data collection from registers do not constitute genuine research; such research could be carried out by even an 8 grader!